The dynamic phenomena of strékan music from colonial to contemporary era in Situbondo (Department of Drama, Dance and Music, FBS, Universitas Negeri Semarang, 2017)
This research is an anthropology of music which discusses the dynamics of strékan music from colonial to contemporary era in Situbondo. In Situbondo, strékan is a term which refers to music for welcoming guests. By ethnography method and postcolonial perspective, this research will discuss social problems and phenomena of strékan music. The result of this research shows that a change of strékan music signifies a change of social condition in Situbondo. In colonial era strékan is assumed by people like music for elite class. The field data show that there is unequal power relation between colonized and colonizer. In pasca-colonial era the hierarchy relation becomes ambivalent. It appears negotiation space between colonial signs and Madurese culture of Situbondo people, considered to be symbolic resistance. Strékan music is reinterpreted as music for low class. In the contemporary era, strékan music tends to market oriented. Strékan music includes dangdut music, following market taste as a consequence of commercialization of art.